2021
DOI: 10.1039/d0cp06326f
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism at the interface of non-magnetic Cu and C60

Abstract: The signature of magnetism without a ferromagnet in a non-magnetic heterostructure is novel as well as fascinating from fundamental research point of view. It has been shown by Al’Mari et...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…89 Three different directions of the STO crystallographic plane modulate the magnetism differently, showing a striking resemblance with charge contrast. The LSMO/STO(100) and LSMO/ STO (111) interfaces have similar charge contrast and show similar magnetization enhancement, while the charge contrast of the LSMO/STO (110) interface is different from the other two interfaces and shows different magnetization enhancement. This confinement of the changed magnetic region to a very thin interfacial layer shows the possibility of modulating the global magnetism of two-dimensional materials whose dimension is comparable to the thickness of the thin interfacial layer using the interfacial mechanism.…”
Section: Interfacial Magnetic Couplingmentioning
confidence: 99%
See 2 more Smart Citations
“…89 Three different directions of the STO crystallographic plane modulate the magnetism differently, showing a striking resemblance with charge contrast. The LSMO/STO(100) and LSMO/ STO (111) interfaces have similar charge contrast and show similar magnetization enhancement, while the charge contrast of the LSMO/STO (110) interface is different from the other two interfaces and shows different magnetization enhancement. This confinement of the changed magnetic region to a very thin interfacial layer shows the possibility of modulating the global magnetism of two-dimensional materials whose dimension is comparable to the thickness of the thin interfacial layer using the interfacial mechanism.…”
Section: Interfacial Magnetic Couplingmentioning
confidence: 99%
“…The appearance of a ferromagnetic phase at the interface region of the heterostructure between nonmagnetic metallic Cu and non-magnetic molecular fullerene (C 60 ) was reported. 110,111 In the presence of strong interfacial coupling between metallic d orbital and molecular p orbital, ferromagnetism emerged in the interfacial region due to the change in the density of states resulting from charge transfer and interface reconstruction. The induced magnetization was also dependent on the number of Cu/C 60 interfaces in the system as well as the thickness of layers.…”
Section: Interfacial Magnetic Couplingmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Sharangi et al reported ferromagnetism at the C 60 /Cu interface due to the charge transfer between C 60 and Cu. 8 Similarly, charge transfer between S and Au has been reported to cause spin-symmetry breaking, 9 which leads to a spin-polarized state and magnetism at the interface. 10,11…”
mentioning
confidence: 99%
“…C 60 can exhibit ferromagnetism at the interface (known as spinterface) when it is deposited on any ferromagnet 21,22 . Presence of C 60 can modify the magnetic property of the ferromagnetic materials as well as nonmagnetic metal [23][24][25][26][27][28] . However, the low value of SOC in OSC limits them for efficient spin to charge conversion.…”
mentioning
confidence: 99%